Insight into influence of roots on hydrothermal properties of alpine meadow in Tibetan Plateau - Hou, Min; Zhang, Zhihong; Wang, Xia (Frontiers in Environmental Science, 2023)
The physical and mechanical behavior of alpine meadow in Tibetan Plateau is now attracting widespread attention. In this paper, a series of experiments were conducted to study the influence of roots on hydrothermal behavior of alpine meadow located at Nangqian district, in the east of Tibetan Plateau, China. Root biomass, physical properties and hydrothermal properties were measured at a soil depth of 0–25 cm. The results showed that the root biomass within the depth of 0–15 cm accounts for 86% of the total root biomass. With the increase of soil depth, the root biomass shows a decreasing trend. The hydraulic conductivities and thermal conductivities of alpine meadow soil increase with the decrease of root biomass. There are lower hydraulic conductivity and thermal conductivity of swallow soil (0–5 cm) than that of deep layer soil. For the bottom soil layer, swallow alpine meadow acts as a “cap” and plays a function of ecological barrier of reducing water infiltration and heat transfer. Under the background of global warming, this insight is helpful to understand the relationship between soil hydrothermal properties and natural disasters in Tibetan Plateau.